FEATURES OF PROTEIN CLAUDIN 11 EXPRESSION AND CONDITION OF BLOOD-TESTIS BARRIER AT VARIOUS FORMS OF MALE INFERTILITY - Базалицька, С.В. (World of Medicine and Biology, 2015)
Molecular recent studies have found that the transmembrane protein family claudins form the basis of intercellular tight junctions forming tissue barriers, including - blood-testis barrier that exists in the male reproductive system. Recent studies have shown that protein Claudin 11 expressing predominantly in tight junctions between Sertoli cells plays an important role in the regulation of blood-testis barrier and can serve as a marker of blood-testis barrier state and spermatogenesis in male infertility of various etiologies. The aim. To determine the blood-testis barrier features state for the immunohistochemical expression of protein Claudin 11 in patients with obstructive and secretory forms of male infertility. Materials and methods. Immunohistochemical (IHC) features of an expression of protein Claudin 11 in testicular tissue of 28 patients with obstructive and secretory forms of male infertility are studied. IHC analysis conducted using a standard avidin-biotin method. For IHC study biopsies were fixed in buffered 12% formalin, embedded in paraffin and sections thickness of 5 mm. Sections were incubated with primary antibodies Claudin 11 (DAKO, Glostrup, Denmark) at a dilution of 1:50. Prevalence and intensity of their reactions were assessed by semiquantitative method. Prevalence of reaction or the number of stained nuclei or cytoplasm of cells evaluated from 0 to 3 points on the following criteria: 0 - no visible staining cells, 1 - less than 10% stained cells, 2 - stained by more than 10% but less than 50% of cells, 3 - stained more than 50% of the cells of the cell layer. The intensity of staining nuclei or cytoplasm evaluated on the following criteria: 0 - no visible staining, 1 - slightly stained nucleus or cytoplasm, 2 - moderately stained nucleus or cytoplasm, 3 - intensely stained nuclei or cytoplasm. The overall result IHC reaction was determined by immunohistochemical quotient (IHCQ) from 0 to 9 points, which is obtained by multiplying estimates of prevalence and intensity of staining. Conducted statistical analysis of the results. Resalts of research. Identified in our study features IHC expression of protein Claudin 11 that are characteristic of different forms of male infertility, statistically significant decrease in cytoplasmatic expression IHCQ in Sertoli cells (7,4±0,45; 5,3 ±0,42; 0,8±0,6) and endothelial cells (7,2±0,45; 5,3 ±0,42; 0,8±0,6) in patients with secretory form of male infertility and blocked of spermatogenesis in spermatogonia, spermatocytes, spermatids, including syndrome "only Sertoli cells", compared to patients with obstructive infertility (р≤ 0,001), are showed. Reducing IHC expression of protein Claudin 11 in secretory form of male infertility and the syndrome of "only Sertoli cells" indicates the blood-testis barrier significant violations that are the basis of additional immune component and deepening of pathological changes in testicular tissue of patients with these forms of male infertility. For morphological study testicular biopsy advisable to determine the status of blood-testis barrier for IHC expression of protein Claudin 11 as an important diagnostic and prognostic indicator of blood-testis barrier condition that can determine the presence or absence of immune component and choose pathogenesis of male infertility caused by treatment and correction of irregularities in each case and determine the further prognosis for recovery of spermatogenesis. Conclusions. Authentic depression of level IHC of an expression of protein Claudin 11 at the secretory form of male infertility and a syndrome «only Sertoli cells» is taped in comparison with obstructive form of male infertility. Results testify to appreciable disturbances of blood-testis barrier, which a basis of development additional immune component and excavation of pathological changes in patients at the secretory form of male infertility.